QUANTITATIVE ANALYSIS OF TENDON ECM DAMAGE USING MRI - Szilagyi, T; Harvey, A; Brady, M; Cochlin, L; Joshi, N; IEEE (2010)
There is a growing demand for non-invasive methods to diagnose tendon injuries and monitor the healing processes of their repair. One particular target is to assess the quality of tendon tissue, which requires imaging modalities, such as Magnetic Resonance Imaging (MRI), that capture structural features of the extracellular matrix (ECM). However, to date there has been limited understanding of the physiological source of intratendinous MRI signal. This paper presents a novel image analysis method, based on low level features, which capture the intrinsic structural properties in order to identify ECM damage. More specifically, continuous intrinsic dimensionality (ciD), based on local image descriptors and derived from the monogenic signal, is used to examine the disruption of 1D structures. The damage measure is summarized using confidence values derived from the bi-modality of local non-parametric probability density functions. Areas of normal and disrupted ECM are detected on MR images of healthy and damaged samples. ©2010 IEEE.